IT Services Quality Measurement Using IT SERVQUAL at University X - Putri, Tantri Febiara; Nugraha, Fida Nirmala; Pratami, Devi; Suwarsono, Litasari (International Journal of Innovation in Enterprise System, 2018)
Information technology plays a major role to enhance service activities in organizations as well as in higher educational institutions / universities.  A special unit (Sisfo) at University X is dedicated to handles daily technology-based services. Every year the performance of the unit is evaluated to increase customer satisfaction and yet the result is contradictory. Using balanced scorecard, the result showed that the unit's performance is in a good category, but when it comes to the satisfaction questionnaire the result said otherwise. This puzzling result due to not so appropriate tools of measurement for the unit’ services. This study conducted performance measurement using IT SERVQUAL to tap the perceived service and expected service of the Sisfo Unit’, form the eyes of the students as the largest customers, on the 6 dimensions: tangibles, responsiveness, reliability, assurance, emphaty and usability. Service dimensions that require immediate action are physical facilities such as hardware and software that are up to date, and processes related to academic activities such as failure to enter into a system, card recording errors, and students’ presence list errors.